(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
The article analyzes the state of the labor market of Uzbekistan and its development trends. As a factor of effective use of available labor resources, labor migration, its impact on the situation in the labor market and problems related to it are studied. Directions for promoting productive and efficient employment by creating new jobs have been developed.